If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-6x + 6) = 96 Reorder the terms: 2(6 + -6x) = 96 (6 * 2 + -6x * 2) = 96 (12 + -12x) = 96 Solving 12 + -12x = 96 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -12x = 96 + -12 Combine like terms: 12 + -12 = 0 0 + -12x = 96 + -12 -12x = 96 + -12 Combine like terms: 96 + -12 = 84 -12x = 84 Divide each side by '-12'. x = -7 Simplifying x = -7
| X+(X*0.2)=101167200 | | 6x^2-13xy-28y^2=0 | | X+(X*0.2)=12 | | y=0.18x^3-2.16x^2+4.86x | | t+7-13=-4 | | sin(3x-30)=0.6 | | 4A-20=22 | | -6(7+X)=-42 | | 7.3+z=60 | | 10a+15b=2x | | 2x+10=-3x | | 2x+5*3=11 | | 2ln(2*x+1)-3ln(x+1)+ln(x+1)=0 | | 3x+18=3x+34 | | 2(4-5x)=7-5(x-2) | | 20+1d=30+.5d | | 4n+3m=11 | | -30=5w+5 | | 64=9u-u | | 103+5x=63 | | 2(x)=54 | | x/-6=120 | | 2y+16=48 | | 2x-2-3=21-34x | | 31+4x=86 | | xln(x)-1=0 | | -54-8x=2x | | (1.09^x)/50 | | 4/5/5/4= | | v=1/3*b*h | | 7n-3n=3n+15 | | 3-12x+18=33 |